Synthesis of Bifunctional Lipoxin‐Derived Enzyme‐Triggered CO‐Releasing Molecules (LipET‐CORMs). Issue 9 (7th February 2023) - Hemmersbach, Lars; Adam, Ruth; Plevnali, Christina; Zhang, Xinmiao; Yard, Benito; Schmalz, Hans‐Günther
Abstract: In an attempt to develop new anti‐inflammatory agents which act by co‐release of carbon monoxide (CO) and a specialized pro‐resolving mediator, we designed conjugates of a lipoxin A4 analogue and an acyloxycyclohexadiene‐Fe(CO)3 complex as an esterase‐triggered CO‐releasing molecule (ET‐CORM). After adjustment of the protecting group strategy, two of such compounds were successfully prepared by total synthesis (12 steps; 4–5 % overall yield) starting from deoxy‐d ‐ribose and exploiting a Wittig olefination and an intermolecular Heck reaction as key C−C bond‐forming steps. A crucial late reduction of an aryl‐ketone moiety in the presence of a highly sensitive dienol ester functionality was achieved with BH3 ‐SMe2 in the presence of catalytic amounts of NaBH4 . Both target compounds were dose‐dependently toxic towards cultured human umbilical vein endothelial cells (HUVEC), with LipET‐CORM 1‐A being slightly more toxic. While induction of heme oxygenase 1 (HO‐1) in HUVEC was observed for both compounds, they did not inhibit TNF‐α‐mediated VCAM‐1 expression in these cells. In M2 polarized macrophages HO‐1 expression was more pronounced as compared to M1 polarized macrophages. In both types of macrophages HO‐1 expression was downregulated by lipopolysaccharide, but only in M2 macrophages HO‐1 expression was rescued by LipET‐CORM. 15‐Lipoxygenase (15‐LO) was only expressed in M2 macrophages and was not influenced by LipET‐CORM. Collectively our data demonstrate that LipET‐CORMs induce HO‐1 expression in endothelial cells and M2 polarized macrophages. The role of the intra‐cellular released lipoxin A4 in resolution of inflammation, however, remains to be assessed. Abstract : Exploratory drug design: To test whether a conjugate of an esterase‐triggered CO‐releasing molecule and a lipoxin analog would exhibit superior biological properties, two such LipET‐CORMs were prepared by chemical synthesis and their anti‐inflammatory potential was investigated in cellular assays.